Ekspresi morfologi tiga jenis jeruk sebagai indikator ketahanan terhadap serangan Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) - Susi Wuryantini; Otto Endarto; Muhammad Ihsan; Hasim Ashari (Perhimpunan Entomologi Indonesia, 2022)
One of the important pests of citrus seeds is citrus silver mites (CSM) Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae). This study aimed to examine the effect of CSM attack on leaf morphology and resistance level of three citrus species. Three types of citrus, namely Tangerine, Mandarin, and Sweet Orange were used as test plants. The shoots of the three types of citrus were tested for nutritional content and five CSM individuals were invested on young leaves that were approximately 10 days old. Observations of CSM population were made 7 days after the investment (DAI) and further observations were carried out every 4 days. The results showed that the lowest abundance of TPJ at 23 DAI was found in type of Tangerine (0.5 ± 0.38 individual) and Mandarin (0.25 ± 0.16 individual). The population of CSM increased at 11 to 15 DAI, and began to decline at 19 DAI. Based on the Pearson correlation analysis, the abundance of CSM was influenced by the fat content and crude fiber content of the leaves. Observations also showed that the Sweet type was more resistant than other types. It can be concluded that the Sweet Orange is more resistant than the Tangerine and Mandarin species.